Phytochemical Studies of Mussaenda hainanensis Merr. - YUAN, KE; QIAO, WEN-TAO; YIN, MING-WEN (Asian Journal of Chemistry, 2010)
Present study reports the chemical constituents of Mussaenda hainanensis Merr. The compounds were isolated by silica gel column chromatography and Sephadex LH-20 methods. Their structures were identified by physicochemical properties and spectroscopic analysis. Twelve compounds were elucidated as xanthone (1), eugenol (2), 3,5- dimethoxy-4-hydroxy-benzaldehyde (3), hydroquinone (4), cinnamaldehyde (5), trans-phytol (6), β-sitosterol (7), stigmasterol (8), ursolic acid (9), oleanolic acid (10), 2α,3β,19α,23-hydroxytormentic acid (11) and rutundic acid (12).